A cone-beam computed tomography study of apical and mental foramen's location in mandibular premolars - Azadeh Harandi; Ehsan Moudi; Hemmat Gholinia; Mehdi Akbarnezhad (Babol University of Medical Sciences, 2018)
Introduction: Knowledge of the internal anatomy of the tooth, apical foramen (AF) and mental foramen (MF) is considered a basic prerequisite before root canal surgical and non-surgical treatments. The aim this study is evaluation the distance and situation of AF & MF to anatomic apex of mandibular  premolar. Materials & Methods: In this cross-sectional study, CBCT images of mandibular premolars from 240 patients with a minimum age of 20 years were evaluated. The location and distance of the MF and AF from the anatomical apex in mandibular premolars were investigated. The information was compared in both genders and both sides of mandible, and analyzed using ANOVA, Chi-Square and T-Test. Results: In the right quadrant, the mean distance from AF to the anatomic apex in the first premolars was higher than the second ones (p=0.02). There was a significant difference among the mean distances from AF to the anatomic apex in various positions of the AF in both quadrants. The MF was closer to the second premolars in both sides (p<0.00). No significant difference was observed between two genders  and two sides of the jaw. Conclusion: possibility of lateral extrusion of canals in the mandibular premolars , the use of the auxiliary devices such as apex locator is useful. According to different place of MF,it’s necessary to pay attention to this position during the periapical surgeries in the mandibular premolars, specially in second premolar.